THE IMPORTANCE OF “HEAVENLY HORSES” IN RELATIONS BETWEEN THE STATES OF DAVAN AND CHINA - Ibrohimov Nozimjon Ixtiyorovich (Journal of new century innovations, 2023)
Annotation: This article analyzes the economic and political relations between Davan and the state of China on the basis of sources, especially the importance of Fergana's “heavenly horses”in relations between the two states.